Cadastre in land market structure - Perovych, L.; Muzyka, N. (Видавництво Львівської політехніки, 2016)
Purpose. Periodic prolonging of the moratorium on sale of agricultural lands does not solve the basic problem of land reform - free circulation of land in order to improve welfare of the population, increasing of social and economic development of territories through the development of new economic, financial and credit inter-farm linkages and mechanisms. Certain prerequisites of land market functioning, defining its function before this should be formed on the legislative and regulatory framework. According to the above, the objective function is defined as a combination of economic, technical, administrative and other actions, events, decisions, etc. on efficient and rational use of agricultural lands in the context of maximizing the social and financial status of the population of the territory. Methods. The research based on the method of analytical analysis of financial and economic activity of agricultural enterprises in different periods; structures and forms of financial and credit system; principles of formation of agricultural enterprises. Results. As a result of conducted research It was highlighted the major shortcomings of introduction of circulation of agricultural lands, which constrain their market. In this regard, it was developed recommendations for creating of the effective functioning of land market. This includes: the development of a number of legislative and regulatory acts that would improve the system of collection cadastral and land planning documentation; develop effective mechanisms of agricultural crediting; form an effective advisory service of land and property relations. Scientific novelty consists in development of new approaches to creation of land market, based not on deriving the maximum profit but meet the needs of the population. Practical significance. Given in the article conclusions and recommendations can be used by the legislative and executive authorities in creating mechanisms for the effective functioning of real estate markets. Мета. Періодичне продовження мораторію на продаж земель сільськогосподарського призначення не вирішує основного завдання земельної реформи - вільний обіг земель з метою покращення добробуту населення, підвищення соціально-економічного розвитку територій на основі розробки нових економічних, фінансово-кредитних міжгосподарських взаємозв’язків та механізмів. При цьому повинні бути сформовані на законодавчому та нормативно-правовому рівні певні передумови функціонування ринку земель, визначивши перед цим його функцію. Відповідно до вищезазначеного, цільова функція визначається як сукупність економічних, технічних, управлінських та інших дій, заходів, рішень тощо щодо ефективного та раціонального використання земель сільськогосподарського призначення в контексті максимального підвищення соціально- матеріального стану населення території. Методика. В основу досліджень покладені методи аналітичного аналізу фінансово-господарської діяльності сільськогосподарських підприємств у різні періоди; структури та форми організації фінансово-кредитної системи; принципи формування агропідприємств. Результати. В результаті проведених досліджень висвітлені основні недоліки впровадження обігу земель сільськогосподарського призначення, які стримують їх ринок. У зв’язку з цим розроблені рекомендації щодо створення перед¬умов ефективного функціонування ринку земель. Це зокрема: розробка багатьох законодавчих та нормативно-правових актів, які б дали змогу удосконалити систему збору кадастрової та землевпорядної документації; розробити ефективні механізми кредитування сільгоспвиробників; сформувати ефективну консультативну службу із земельно-майнових відносин. Наукова новизна полягає у розробці нових підходів до формування ринку землі, які базуються не на отриманні максимальних прибутків, а на задоволенні потреб населення. Практичне значення. Наведені в статті висновки і рекомендації можуть бути використані органами законодавчої та виконавчої влади під час створення механізмів ефективного функціонування ринків нерухомості. Цель. Периодическое продления моратория на продажу земель сельскохозяйственного назначения не решает основной задачи земельной реформы - свободное обращение земель с целью улучшения благосостояния населения, повышение социально-экономического развития территории на основе развития новых экономических, финансово-кредитных межхозяйственных взаимосвязей и механизмов. При этом должны быть сформированы на законодательном и нормативно-правовом уровне определенные предпосылки функционирования рынка земель, определив перед этим эго функцию. Согласно вышеуказанному, целевая функция определяется как совокупность экономических, технических, управленческих и иных действий, мероприятий, решений и т.п. по эффективному и рациональному использованию земель сельскохозяйственного назначения в контексте максимального повышения социально-материального положения населения территории. Методика. В основу положены методы аналитического анализа финансово-хозяйственной деятельности сельскохозяйственных предприятий в различные периоды; структуры и формы организации финансово-кредитной системы; принципы формирования агропредприятий. Результаты. В результате проведенных исследований освещены основные недостатки введения оборота земель сельскохозяйственного назначения, сдерживающих их рынок. В связи с этим разработаны рекомендации по созданию предпосылок эффективного функционирования рынка земель. Это в частности: разработка ряда законодательных и нормативно-правовых актов, которые бы разрешили усовершенствовать систему сбора кадастровой и землеустроительной документации; разработка эффективных механизмов кредитования сельхозпроизводителей; формирование эффективной консультативной службы с земельно-имущественных отношений. Научная новизна заключается в разработке новых подходов к формированию рынка земли, которые базируется не на получении максимальной прибыли, а на удовлетворении потребностей населения. Практическое значение. Приведены в статье выводы и рекомендации могут быть использованы органами законодательной и исполнительной власти при создании механизмов эффективного функционирования рынков недвижимости.
Кадастр у структурі ринку земель
Кадастр в структуре рынка земли
Keywords: market of agricultural lands; market; credit; ринок сільськогосподарського призначення; ринок; кредитування; рынок сельскохозяйственного назначения; рынок; кредитование